Standard Establishment to Improve Performance Implementation of Standards of Internal Quality Assurance Systems of Private Universities (IQSA PU) - Abdus Syukur, Imron; Suherman, Dadang; Gaffar, M. Andriana; Mardiana, Dinny (International Journal of Educational Research & Social Sciences, 2022)
The title of this research is : "Standard Establishment To Improve Performance Implementation of Standards of Internal Quality Assurance Systems Private Universities”,  motivated by the fact that the IQAS Standards in private universities generally have not been able to increase the IQAS performance of private universities. This study aims to describe and analyze IQAS in private universities to improve the performance of the IQAS of UNBIS Standard Implementation and is based on: a) theories: System, Goal Setting, basic concepts: Good Vision and Mission, and ISO 21001:2018 Management Model. Descriptive exploratory method with a qualitative approach of case study type has been used in this research, and this is to focus on one particular object as a case and make general conclusions according to scientific facts. The results of the research in general have described the Establishment of IQAS of UNBIS Standards for improving the performance of the Implementation of the IQAS of UNBIS Standards and specific conclusions that: 1) The rationale and background for the preparation of the Organization's Vision and Mission in order to improve the performance of the implementation of the IQAS Standards of UNBIS has been established, and socialized to the stakeholders. The Standard Establishment to improve the Performance of Implementation of IQAS UNBIS Standards has been implemented. Management principles, policies,  purpose, goal achievement strategy in Standard Implementation to improve the performance of the UNBIS IQAS Standard have been implemented intergratedly by the  the parties involved in UNBIS. The Outputs of Standard Establishment to improve the Performance of Implementation of IQAS of UNBIS Standards have been achieved. The efforts to overcome obstacles in setting standards to improve the performance of the implementation of IQAS Standards have been  identified.